2022
DOI: 10.3389/fpsyt.2022.891479
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Insulin Resistance in a Sample of Adult ADHD Outpatients

Abstract: BackgroundHigh prevalence of Metabolic Syndrome (MS) was found in patients with schizophrenia and bipolar disorders. Insulin Resistance (IR) seems to mediate MS role in developing cardiometabolic consequences.AimsTo investigate the prevalence of MS, and the role of MS components and IR surrogate indexes in determining MS in adult ADHD outpatients.MethodsIn the present cross-sectional study, MS, defined according to the Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults (ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Our study found a positive correlation between serum glucose levels and hyperactivity. Other studies suggest a possible link between ADHD and other factors related to IR [ 36 , 37 ]. This may be due to common risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found a positive correlation between serum glucose levels and hyperactivity. Other studies suggest a possible link between ADHD and other factors related to IR [ 36 , 37 ]. This may be due to common risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While there is some evidence suggesting a link between ADHD and IR, direct and consistent evidence is limited. The study by di Girolamo et al [ 37 ] examines the relationship between ADHD and metabolic syndrome (MS) in adults. The study, conducted in Italy, examines the role of MS components and IR indices in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Partially linked with mitochondrial dysfunction, the energy metabolism imbalance in ADHD has been discussed as a possible source of neurodevelopmental delays ( Cannon Homaei et al, 2022 ; Foschiera et al, 2022 ; Radtke et al, 2022 ). Cerebral glucose hypometabolism has been found in childhood-onset adult ADHD patients ( Zametkin et al, 1990 ), however, this may also be a consequence of deficits in impulse control leading to metabolic syndrome ( di Girolamo et al, 2022 ). Indeed, a recent meta-analysis found a bidirectional association between ADHD and T2DM ( Ai et al, 2022 ), pointing to long-lasting BIR effects.…”
Section: Attention-deficit Hyperactivity Disorder Current Genetic And...mentioning
confidence: 99%
“…In addition, to promote the applicability of imaging findings and allow the identification of robust predictors of individual variation in responses, these studies must take care to include minority populations with disproportionately high obesity rates, which are often under-represented in imaging studies. The comorbidity of obesity and MetS 149 , 150 with psychiatric and neurodevelopmental disorders 151 , 152 (e.g., depression, attention deficit hyperactivity disorder ADHD) 153 , 154 also deserves further attention. For example, increasing evidence suggests that ADHD and obesity share neural and genetic underpinnings 155 , 156 and thus findings of studies that do not screen out individuals with ADHD symptoms may be driven in part by a subset of individuals with both obesity and ADHD symptomatology who may not be wholly representative of the larger population.…”
Section: Future Directionsmentioning
confidence: 99%